2013
DOI: 10.1371/journal.pone.0076716
|View full text |Cite
|
Sign up to set email alerts
|

Ulmus davidiana var. japonica Nakai Upregulates Eosinophils and Suppresses Th1 and Th17 Cells in the Small Intestine

Abstract: The bark of Ulmus davidiana var. japonica Nakai (Ulmaceae) has been used in traditional Korean medicine for chronic inflammation in the gastrointestinal tract. Here we investigated the frequency and cytokine profile of the major immune cells in the small intestinal lamina propria (SI LP), spleen, and mesenteric lymph nodes (MLNs) of mice treated orally with Ulmus davidiana var. japonica Nakai bark water extract (UDE) to address the immunomodulatory role of this herb in intestinal homeostasis. B6 mice were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Supporting this finding, the extract of Ulmus davidiana var. japonica Nakai up-regulates eosinophils and reduces the frequencies of Th1 as well as Th17 cells in the small intestine ( Lee et al, 2013 ). Contrary to eosinophil-deficient ΔdblGATA-1 mice, IL-1Ra–deficient mice did not show a significant increase of Th1 cells in the small intestine ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this finding, the extract of Ulmus davidiana var. japonica Nakai up-regulates eosinophils and reduces the frequencies of Th1 as well as Th17 cells in the small intestine ( Lee et al, 2013 ). Contrary to eosinophil-deficient ΔdblGATA-1 mice, IL-1Ra–deficient mice did not show a significant increase of Th1 cells in the small intestine ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The extract of Ulmus davidiana var. japonica Nakai increases the number of small-intestinal eosinophils and suppresses differentiation and/or proliferation of Th1 and Th17 cells ( 40 ). Regulatory eosinophil-recruiting prebiotics or probiotics may be useful for prevention of inflammatory and metabolic diseases.…”
Section: Prospectsmentioning
confidence: 99%
“…Previous research indicated that UD extracts had various ameliorative effects on acute inflammatory responses in rats [9,10], osteopenia [11], and an in vitro model [12]. Similarly, the supercritical fluid of UD had anti-inflammatory, anti-angiogenesis [13], and anti-melanin effects [14].…”
Section: Introductionmentioning
confidence: 99%